2014
DOI: 10.1155/2014/704323
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes for Breast Cancer Patients Undergoing Mastectomy and Reconstruction with Use of DermACELL, a Sterile, Room Temperature Acellular Dermal Matrix

Abstract: Background. Decellularized human skin has been used in a variety of medical applications, primarily involving soft tissue reconstruction, wound healing, and tendon augmentation. Theoretically, decellularization removes potentially immunogenic material and provides a clean scaffold for cellular and vascular in growth. The use of acellular dermal matrix in two-stage postmastectomy breast reconstruction is described. Methods. Ten consecutive breast cancer patients were treated with mastectomies and immediate reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Recent innovation in the treatment of full-thickness defects has been the use of dermal substitutes. [19][20][21][22][23][24][25] The use of STSG combined with a layer of ADM underneath provides an additional layer of tissue coverage and the potential benefit of promoting wound healing while providing vital tissue support for STSG; it can especially be useful in tendon augmentation offering tissue support while also providing the missing mechanical properties to the open wound site. 25 The mechanical support provided by the ADM reduces the risk of reinjury of the tendon in repair procedures such as rotator cuff repair and the management of Achilles tendon ruptures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Recent innovation in the treatment of full-thickness defects has been the use of dermal substitutes. [19][20][21][22][23][24][25] The use of STSG combined with a layer of ADM underneath provides an additional layer of tissue coverage and the potential benefit of promoting wound healing while providing vital tissue support for STSG; it can especially be useful in tendon augmentation offering tissue support while also providing the missing mechanical properties to the open wound site. 25 The mechanical support provided by the ADM reduces the risk of reinjury of the tendon in repair procedures such as rotator cuff repair and the management of Achilles tendon ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Certainly the introduction of advanced wound care technologies, including negative pressure wound therapy (NPWT) and bioengineered tissues such as acellular dermal matrices (ADMs), has reduced the need for complex surgical procedures with the right indication. [15][16][17][18][19][20][21][22][23][24] The use of an ADM underneath split thickness skin grafts (STSGs) provides an additional thick layer at the wound bed, promoting wound healing while providing vital tissue support for STSG, improving the mechanical and functional properties of coverage. [25][26][27][28][29] A 2-step procedure is the most common approach, where the coverage by a STSG is performed after the ADM is fully integrated.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies can provide initial insight, but more reliable data can be obtained from clinical studies. While clinical studies are more difficult to come by for this topic, a few studies have been reported that conducted a histological analysis on biopsies taken from implanted M-ADM used in breast reconstructions for breast cancer patients undergoing mastectomies (Bullocks 2014 ; Vashi 2014 ; Yu et al 2016 ). Bullocks ( 2014 ) focused on the clinical outcomes in a ten patient case series which also included biopsies taken from human ADMs: M-ADM (also described in the study as DermACELL), AlloDerm, and FlexHD.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that faster ADM incorporation, indicated by rapid recellularization and revascularization, could result in fewer complications in breast reconstruction surgery, though the results of this 10 patient (18 reconstructions) case series should not be generalized. While there was no comparator ADM in Vashi ( 2014 ), two dermatopathologists identified recellularization marked by fibroblasts, an abundance of elastin, and robust vasculature in biopsy samples of M-ADM (also described in the study as DermACELL) taken at 16 weeks post-implantation. Yu et al ( 2016 ) carried out a study in which 48 ADM and non-ADM breast capsule biopsy specimens from 15 patients were histologically analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In current practice, the selection of ADM is usually based on surgeon preference, hospital budgets and negotiated vendor contractual agreements. Despite differences in their level of sterility, consistency and thickness of the biologic material as well as cost, we are unaware of any prospective randomized trials comparing them directly [ 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%